Estudio Socio-Jurídico de la Influencia de los Estigmas Sociales en los casos de Violencia Doméstica Masculina en Ecuador - Medina Paccha., Gabriela Jackeline (2024)
Social stigmas are labels that relate people to favorable or unfavorable characteristics according to their behaviors; they have become deeply rooted in the culture and tradition of societies around the world, influencing the way in which individuals, whether men or women, develop and are accepted in their social environment. In the case of male domestic violence, stigmas have led to its invisibility and lack of attention, becoming a way of justifying impunity. Currently, violence by women against men in the domestic sphere is a reality that has not yet been accepted or adequately addressed by the Ecuadorian legal framework. Since ancient times, men have been stigmatized as sexist, oppressors and abusers, making them directly responsible for aggressions against women. By not being seen as a vulnerable figure, he has been deprived of the right to legitimate self-defense, to full reparation, to the adoption of precautionary measures, to have his complaints taken seriously even with sufficient evidence, and to access to effective justice. This research focuses on determining the influence of social stigmas and how they affect men's access to justice when they are victims of domestic violence, despite the fact that Ecuadorian society perceives itself as a guarantor of rights and justice, as established in Article 1 of the Constitution of the Republic of Ecuador (CRE). The lack of applicability of the constitutional principles enshrined in Article 3, paragraphs 1, 3, 5 and 8, on the duties of the State in terms of human rights and equality, will be analyzed. Likewise, this problem will be examined in light of other regulatory bodies such as: the Comprehensive Organic Criminal Code (COIP), the Organic Code of the Judiciary (COFJ), the Ecuadorian Civil Code and the Law to Prevent and Eradicate Violence against Women.